Consent for blood transfusion: Do patients understand the risks and benefits?. Issue 5 (28th July 2014) - Cheung, D.; Lieberman, L.; Lin, Y.; Callum, J.
SUMMARY Background and Objectives Blood transfusion is a frequent medical intervention in hospitals. The benefits of, risks of and alternatives to blood transfusions are not consistently understood by patients. The objective of this study was to assess gaps in knowledge and comfort with the current process of consenting patients for blood transfusions. A standardised video regarding the risk and benefits of blood transfusions was developed and feedback regarding this tool was assessed. Methods After informed consent had been obtained, 25 patients receiving their first transfusion at a single academic centre were asked to complete a survey, watch a standardised educational video and complete a follow‐up survey. Results The patient survey revealed that the information recollected from informed consent discussions was variable and incomplete. After the informed consent discussion, the majority of patients were comfortable with having a blood transfusion, although one‐third did express concerns or worry about having a blood transfusion. After viewing the video, patients felt that the video improved their understanding of the risks (7·3 of 10), benefits (6·9 of 10) and alternatives (7·1 of 10) to transfusion, but it did not change their comfort with blood transfusion consent. Conclusion Patients experienced a variable informed consent process prior to blood transfusion. Although the video improved their understanding of risks, it did not improve patient comfort towards giving consent for transfusion as the level of comfort was already high. The video is available online (http://www.youtube.com/watch?v=RxaPnLkgh‐0) as an optional resource for patients (and physicians) who wish to receive standardised and accurate information about blood transfusions.